Pathergy Phenomenon - Ergun, Tulin (Frontiers in Medicine, 2021)
Skin pathergy reaction (SPR) is a hyperreactivity response to needle-induced trauma, characterized by a papule or pustule formation, 24-48 hours after sterile-needle prick. It is affected by a wide array of factors, including the physical properties of the needles being used, the number of pricks, and disease-related factors such as male gender, active disease. There is a remarkable variation in reactivity among different populations with a low positivity rate in regions of low prevalence like Northern Europe, and higher prevalence mainly in communities living along the historical Silk Road, like Turkey, China, and Middle Eastern countries. SPR is not constant during the disease course, has lost its sensitivity over decades, and can be positive in various disorders such as Sweet's syndrome, pyoderma gangrenosum, Crohn's disease, A20 haploinsufficiency, deficiency of IL-1-receptor antagonist, and few others. Nevertheless, it is a criterion included in many currently used diagnostic or classification criteria for Behçet's disease. Although, not being fully uncovered yet, available data points to the activation of both innate and adaptive immune systems with an inflammatory response mediated by polymorphonuclears and T-cells. In addition to its utility in diagnosing Behçet's Disease, SPR may serve as a model for investigating the inflammatory pathways involved in the etiopathogenesis of this complex disease.